Penjadwalan Produksi Bordir Kain Di CV Djarum Mulia Embroidery - Endro Prihastono; Khaerudin . (Jurnal Ilmiah Dinamika Teknik, 2015)
Scheduling is sort manufacture/ workmanship of the product thoroughly done on multiple machines. Thus the problem sequencing (sequencing) always involves supply number of components that are often referred to as a job. Job himself is still a composition and a number of basic elements called activities or operations. The production process of existing border cloth CV. Djarum Mulia Embroidery is divided into two divisions of production which is a division 1 and division 2 garment while the division is a division local.di each division is divided into several mutually job sequence to produce embroidery products. Keywords : Scheduling, Production